The Impact of Trade Liberalisation on Export Growth and Import Growth in Sub-Saharan Africa - Lanre Kassim (University of Kent, School of Economics, 2013)
This paper adopts panel data methodologies to investigate the impact of trade liberalisation on export growth and import growth across 28 Sub-Saharan African countries from 1981 to 2010. We find that trade liberalisation increases the growth of exports, however, imports grow faster by approximately two percentage points which gives a prima facie evidence that the trade balance in the region deteriorated in the post-liberalisation era. We also find that trade liberalisation significantly raises the price elasticity of demand for exports and imports, however, it does not significantly affect income elasticity of demand.
Keywords: C23; F13; F14; O55; 330; Trade liberalisation; Export growth; Import growth; Price and Income elasticities of demand; Sub-Saharan Africa